2022
DOI: 10.1021/acs.accounts.2c00135
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobase-Interaction-Directed Biomimetic Supramolecular Self-Assembly

Abstract: Conspectus The design and fabrication of synthetic self-assembled systems that can mimic some biological features require exquisitely sophisticated components that make use of supramolecular interactions to attain enhanced structural and functional complexity. In nature, nucleobase interactions play a key role in biological functions in living organisms, including transcription and translation processes. Inspired by nature, scientists are progressively exploring nucleobase synthons to create a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 59 publications
0
39
0
Order By: Relevance
“…To provide matrixes with tunable chemical compositions, more complex structures, and higher precision, we suggest different assembly techniques should be used synergistically. For example, because the self-assembly of biocompatible nanoparticles can be precisely controlled, , by using the nanoparticle self-assembly technique and 3D printing technique together, complex hierarchical structures could be constructed . There are plenty of combinations of assembly techniques yet to be investigated. , …”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…To provide matrixes with tunable chemical compositions, more complex structures, and higher precision, we suggest different assembly techniques should be used synergistically. For example, because the self-assembly of biocompatible nanoparticles can be precisely controlled, , by using the nanoparticle self-assembly technique and 3D printing technique together, complex hierarchical structures could be constructed . There are plenty of combinations of assembly techniques yet to be investigated. , …”
Section: Discussion and Future Perspectivementioning
confidence: 99%
“…26 These studies also showed that the obtained type of morphology can vary when some parameters including the pH or solvent type are changed. 26 Indeed, these parameters affected the H-bonds between nucleobases responsible for the self-assembly and in consequence the self-assembled morphology. The correlation between complementary H-bonds in nucleobase-containing copolymers and their morphology is still under investigation.…”
Section: Introductionmentioning
confidence: 92%
“…18 Similar to the vinylic monomers, the synthesis of cytosine and guanine containing nucleobase copolymers is very complex, and the number of examples of self-assembled architectures made from these polymers are in consequence very limited. 15,26,27 Since most of the examples of self-assembled nucleobase-containing copolymers concern adenine and/or thymine (uracil) derivatives, 26,28 the discussion of this section will focus on monomers containing these nucleobases prepared by SN reactions.…”
Section: A Nucleobase-containing Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The interplay of multiple interactions, [4][5][6][7][8][9] configuration and conformational preference, 4,[10][11][12][13][14] alongside secondary electrostatic interactions [15][16][17] to tune hydrogen-bonding strength, 18,19 has furnished design rules for hydrogen-bonding motifs [20][21][22] and given rise to several that form strongly associated dimers that are widely employed in materials science. 21,23,24 Hydrogen-bonding can be inferred in the solid state using X-ray crystallography or neutron diffraction. [25][26][27][28] Solution-based techniques (UV/vis, NMR and IR) can qualitatively establish that molecular recognition takes place by changes in resonance or vibrational frequency, (e.g.…”
Section: Introductionmentioning
confidence: 99%